Differential eco-physiological performance to declining groundwater depth in Central Asian C3 and C4 shrubs in the Gurbantunggut Desert - Tiemuerbieke, Bahejiayinaer; Ma, Jian-Ying; Sun, Wei (Frontiers in Plant Science, 2024)
Resources in water-limited ecosystems are highly variable and unpredictable, and the maintenance of functional diversity among coexisting species is a crucial ecological strategy through which plants mitigate environmental stress. The comparison of differential eco-physiological responses among co-occurring plants in harsh environments could help provide deep insights into the coexistence mechanisms of competing species. Two coexisting desert shrubs with different photosynthetic pathways (Haloxylon ammodendron and Tamarix ramosissima) were selected in the Gurbantunggut Desert located in northwest China. This study detected variations in the water sources, photosynthetic parameters, stem water status, and nonstructural carbohydrates of the two shrubs at three sites with different groundwater table depths during the growing seasons of 2015 and 2016 to identify distinct eco-physiological performances in coexisting plants with different functional types under fluctuating water conditions. The water sources of H. ammodendron shifted from soil water to groundwater, while T. ramosissima extracted water mainly from deep soil layers at both sites. Significant reductions in carbon assimilation and stomatal conductance in H. ammodendron with deeper groundwater table depth were detected during most drought periods, but no significant decreases in transpiration rate were detected with declining groundwater table depth. For T. ramosissima, all of these gas exchange parameters decreased with the progression of summer drought, and their relative reduction rates were larger compared with H. ammodendron. The stem water status of H. ammodendron deteriorated and the relative reduction rates of water potential increased with deeper groundwater, whereas those of T. ramosissima did not differ with greater groundwater depth. These findings indicated that prolonged drought would intensify the impact of declining groundwater depth on the eco-physiology of both shrubs, but the extent to which the shrubs would respond differed. The two shrubs were segregated along the water–carbon balance continuum; the C3 shrub T. ramosissima maximized its carbon fixation at an enormous cost of water, while greater carbon fixation was achieved with far greater water economy for H. ammodendron. These results demonstrated that the two shrubs prioritized carbon gain and water loss differently when faced with limited water sources. These mechanisms might mitigate competitive stress and enable their coexistence.